2021
DOI: 10.2196/22387
|View full text |Cite
|
Sign up to set email alerts
|

Expectations of Continuous Vital Signs Monitoring for Recognizing Complications After Esophagectomy: Interview Study Among Nurses and Surgeons

Abstract: Background Patients undergoing esophagectomy are at serious risk of developing postoperative complications. To support early recognition of clinical deterioration, wireless sensor technologies that enable continuous vital signs monitoring in a ward setting are emerging. Objective This study explored nurses’ and surgeons’ expectations of the potential effectiveness and impact of continuous wireless vital signs monitoring in patients admitted to the ward … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
(10 reference statements)
1
8
0
Order By: Relevance
“…Current sensors and vital sign trends still do not include factors such as the nurse worry factor and the critical EWS component 'level of consciousness'. [32][33][34] In line with other studies, the value of the nurse's clinical observations in detection of deterioration was also with respect to reservations about a potential decrease in the bedside nurse-patient contacts by using CMVS which may limit the value of their clinical judgement. 15,35,36 Also, nurses strongly valued the role of the physician in trend assessment because of their expertise with vital sign trends interpretation as part of their clinical judgement.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Current sensors and vital sign trends still do not include factors such as the nurse worry factor and the critical EWS component 'level of consciousness'. [32][33][34] In line with other studies, the value of the nurse's clinical observations in detection of deterioration was also with respect to reservations about a potential decrease in the bedside nurse-patient contacts by using CMVS which may limit the value of their clinical judgement. 15,35,36 Also, nurses strongly valued the role of the physician in trend assessment because of their expertise with vital sign trends interpretation as part of their clinical judgement.…”
Section: Discussionsupporting
confidence: 74%
“…Especially, clear criteria to prevent premature transfers of patients from ICU to the general ward with CMVS are needed, which was also was mentioned as a potential worry in another study. 32 Importantly, the multitude of (false) alarms in our study was perceived as excessive, which may cause alarm fatigue and may be a major barrier for successful implementation. In several other studies, nurses also reported frequent (false) alarms to be the biggest disruptive factor for their work processes.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…On the other hand, all kinds of collected data are drawn and displayed, and preliminary analysis and diagnosis are made. If it is judged that there is a critical situation, it will immediately send text messages and automatically dial the alarm for help [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Obviously, nurses’ observations on the patient status and possible clinical deterioration is much more than just monitoring vital signs. Current sensors and vital sign trends still do not include factors such as the nurse worry factor and the critical EWS component ‘level of consciousness’ [ 32 34 ]. In line with other studies, the value of the nurse’s clinical observations in detection of deterioration was also with respect to reservations about a potential decrease in the bedside nurse-patient contacts by using CMVS which may limit the value of their clinical judgement [ 15 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%